Identifikasi low back pain dan kadar asam laktat pada komunitas ojek online di Yogyakarta - Rizky Wulandari; Riska Risty Wardhani (DiscoverSys Inc., 2020)
Background: Occupational diseases are caused by work and work attitudes. One of the spine's occupational diseases is low back pain (LBP), which arises because of a static position in work and is continuous. Fatigue at work can be detrimental to both the workforce and the company. One of the risks of work fatigue is the occurrence of work accidents. Increased pain in low back pain in workers is accompanied by an increase in lactic acid so that the pain is felt related to the level of fatiguePurpose: The study aimed to identify Low back pain and lactic acid levels in the online motorcycle taxi community and to determine the characteristics of Low Back Pain, types of pain, risk factors and levels of lactic acid.Methods: This research is descriptive-analytical using a retrospective approach with total sampling, which describes the socio-demographic percentage of online motorcycle taxis, external factors, LBP characteristics, pain type, and lactic acid levels. We excluded sample with spine dislocation or fracture. LBP specific test was used for LBP examination and lactic acid was measured by Roche Accutrend Plus. The data analysis test was in the form of univariate and bivariate analysis with Kendall's tau-b. P-value <0.05 was significant.Results: The incidence of non-specific LBP was 64.7% and myogenic LBP was 35.3%. There was an increase in lactic acid levels in the online motorcycle taxi community with a mean and standard deviation of 5.19 ± 1.92.Conclusion: The occurrence of LBP and increased levels of lactic acid in the online motorcycle taxi community. For further research, it is hoped that it can add to the respondents' characteristics and the number of respondents more so that a higher correlation relationship is obtained. Latar belakang: Pekerjaan dan sikap selama bekerja dapat menimbulkan penyakit akibat kerja. Nyeri punggung bawah merupakan salah satu penyakit akibat kerja. Nyeri punggung bawah mengenai tulang belakang akibat posisi statis dalam bekerja dan bersifat berkepanjangan. Penyakit akibat kerja akan meningkatkan risiko terjadinya kelelahan kerja. Adanya kelelahan kerja dapat berisiko terjadinya kecelakaan akibat kerja, sehingga merugikan tenaga kerja itu sendiri maupun perusahaan. Peningkatan nyeri punggu bawah pada pekerja disertai dengan peningkatan asam laktat sehingga nyeri dirasakan berhubungan dengan tingkat kelelahanTujuan: Tujuan penelitian yaitu mengidentifikasi nyeri punggung bawah (low back pain) dan kadar asam laktat pada komunitas ojek online di Yogyakarta serta untuk mengetahui karakteristik low back pain (LBP), tipe nyeri, faktor resiko dan kadar asam laktat.Metode: Penelitian deskriptif analitik dengan menggunakan pendekatan retrospektif dengan total sampling, yang menggambarkan persentase sosio-demografis ojek online, faktor ekternal, karakteristik LBP, tipe nyeri, dan kadar asam laktat. Responden dengan riwayat dislokasi atau patah tulang belakang tereksklusi. Tes spesifik LBP untuk memeriksa LBP dan kadar asam laktat diuji menggunakan alat Accutrend Plus Merk Roche. Analisis data berupa analisis univariat dan bivariat dengan kendall’s tau-b. Nilai p<0.05 bernilai signifikan.Hasil: Adanya kejadian LBP non spesifik sebesar 64,7% dan LBP Miogenik sebesar 35,3%. Adanya peningkatan kadar asam laktat dalam komunitas ojek online dengan rerata dan simpangan baku 5,19±1,92.Kesimpulan: Adanya kejadian LBP dan peningkatan kadar asam laktat dalam komunitas ojek online. Untuk penelitian selanjutya diharapkan dapat menambah karakteristik responden dan jumlah responden yang lebih banyak agar diperoleh hubungan korelasi lebih tinggi.